The Relationship between Patients’ Chemotherapy-Induced Peripheral Neuropathy and their Demographic and Clinical Characteristics - Mohammed, Ali Jassim Mohammed; Mohammed, Widad K. Mohammed (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To find out the relationship between patients’ chemotherapy-induced peripheral neuropathy (CIPN) and their demographic and clinical characteristics. Methodology: The study utilized a descriptive cross-sectional design conducted at two oncology centers. A purposive sampling method was used to collect data from 102 breast or lung cancer patients receiving neurotoxic chemotherapy from December 2022 to May 2023. A 20-item EORTC QLQ-CIPN20 scale was used to evaluate CIPN symptoms. The content validity was evaluated by 12 expert, The Cronbach alpha reliability coefficient was 0.8, indicating that the instrument is reliable. Descriptive and inferential analyses approaches was used for the data analysis. Results: The study showed significant statistical differences between patients’ chemotherapy-induced peripheral neuropathy with their age group, chemotherapy, and tumor stage at P < 0.05. Moreover, the results showed a significant statistical positive correlation between patients’ chemotherapy-induced peripheral neuropathy with their number of chemotherapy cycles and cumulative dose at P < 0.05. Recommendation: Conducting future research with a larger sample size would be beneficial and allowing for differentiation the results among participants with different cancer types and varying chemotherapy agents.